SOCIAL INTELLIGENCE: HISTORY OF INCEPTION, DYNAMICS OF POINTS OF VIEW ON ITS ESSENCE AND CONTENT (Psychology Travelogs, 2023)
The issue of determining the essence and content of the social intelligence of specialists who are able to understand themselves and others, their actions, verbal and non-verbal reactions, therefore to interact with the social environment in a high-quality manner is relevant for the study of socialization processes in modern society. The purpose of the study is to analyze and generalize different points of view on its essence and content of a number of domestic and foreign scientists of social intelligence as a psychological phenomenon, that is socially directed on its ontogenetic development and has its own history of origin, multiple definitions and components of its content. The study analyzed the existing concepts of social intelligence, which were clarified and developed by many researchers in the humanitarian sphere, in particular those that were proposed at different times by supporters of different psychological schools. Special attention in the work was paid to the study of social intelligence as a specific cognitive formation that ensures the effectiveness of social activity of an individual, as a specific form of organization of its mental experience in the sphere of social interaction. In addition, the factor of considering the dynamics of understanding its essence and content, it is also relevant that the article emphasizes the importance of defining social intelligence as the adaptation of an individual to human existence, as well as the fact that intelligence acquires value and can be called intelligence only when it acquires important meaning in the social environment. The result of the study was a theory by the authors of the views and ideas of scientists regarding the essence and content of the psychological phenomenon «social intelligence», which, in their common opinion, manifests itself in communication, joint activities, group interaction, management and is described using a system of constructs that affect effectiveness various interpersonal influences.
Keywords: essence; content; social intelligence; social environment; personality; social interaction; communication